2009
DOI: 10.1080/14767050802676717
|View full text |Cite
|
Sign up to set email alerts
|

A significant linear association exists between nuchal translucency thickness and adverse perinatal outcome in euploid fetuses

Abstract: A linear association exists between NT thickness in chromosomally and structurally normal fetuses, and the risk for gestational diabetes and perinatal mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Only few studies have linked increased NT in euploid fetuses with placental‐related adverse outcomes 25 ,. 26 Recently, a large cohort study assessed pregnancy outcomes in 260 unexplained increased nuchal translucency (i.e., fetal structural or chromosomal abnormalities) compared to 5749 normal NT pregnancies 27 . The study group had a slightly, but significantly higher rates of pre‐eclampsia ( p = 0.018), preterm birth ( p = 0.023), fetal growth restriction ( p = 0.032), and low birth weight ( p = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies have linked increased NT in euploid fetuses with placental‐related adverse outcomes 25 ,. 26 Recently, a large cohort study assessed pregnancy outcomes in 260 unexplained increased nuchal translucency (i.e., fetal structural or chromosomal abnormalities) compared to 5749 normal NT pregnancies 27 . The study group had a slightly, but significantly higher rates of pre‐eclampsia ( p = 0.018), preterm birth ( p = 0.023), fetal growth restriction ( p = 0.032), and low birth weight ( p = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Increased NT in euploid fetuses can be due to heart defects, omphalocele, body stalk anomaly, skeletal defects; some genetic syndromes, such as congenital adrenal hyperplasia, fetal akinesia, or Noonan syndrome, have been suggested as possible causes. According to recent studies, a significant correlation has been found between increased NT and the presence of diaphragmatic hernia and a higher risk of cleft palate [12], [13], [14], [15].…”
Section: Possible Pathophysiological Mechanisms Arementioning
confidence: 99%
“…Several studies have demonstrated that increased nuchal translucency (INT) is strongly associated with fetal cytogenetic disorders [1][2][3][4][5], especially trisomy 21 or 45, XO, and some specific fetal anomalies, in particular cardiac defects [3,6,7]. Additionally, INT in euploid fetuses or unexplained INT has been reported to be associated with various poor obstetric outcomes [8][9][10][11][12][13], including spontaneous abortion, low birth weight, preterm birth, fetal growth restriction, gestational diabetes mellitus, and preeclampsia. Nevertheless, most studies concerning effectiveness of NT measure-ments as a screening test of chromosome abnormalities or fetal cardiac defects are confined to the western world, the outcomes of NT screening in developing countries being reported rarely.…”
Section: Introductionmentioning
confidence: 99%